CuBr2‐induced charge screening on photoactive nanocolloidal polypyrrole:poly(styrene sulfonate) composite multilayer thin‐film counter electrodes for high‐efficiency dye‐sensitized solar cells. Issue 5 (18th March 2016) - Maruthamuthu, S; Chandrasekaran, J; Manoharan, D; Karthick, SN; Kim, Hee‐Je; Saravanakumar, B
Abstract : Polypyrrole (PPy):poly(styrene sulfonate) (PSS) counter electrode films were treated with CuBr2 which removed the excess PSS in the films, and as a result of this salt treatment, the plate‐like aggregates of particles were affected, being spread as smaller domains over the entire surface. Increase in roughness is due to the increased grain size after salt treatment which facilitated higher charge transport across the grains. Abstract: Nanocolloidal polypyrrole (PPy):poly(styrene sulfonate) (PSS) particles were synthesized by chemical oxidative polymerization using 15 wt% of PSS. The highly processable polymer composite (PPy:PSS) was spin‐coated at 4000 rpm on fluorine‐doped tin oxide glass and subsequently employed as a counter electrode (CE) for dye‐sensitized solar cells (DSCs). PPy:PSS multilayer (one, three, five) CEs were treated with CuBr2 salt, which enhances the efficiency of the DSCs. Optical studies reveal that a bulkier counterion hinders interchain interactions of PPy which on salt treatment shows a moderate redshift in absorption maxima. Salt‐treated PPy:PSS films exhibit lower charge transfer resistance, higher surface roughness and better catalytic performance for the reduction of I3 −, when compared with untreated films. The improved catalytic performance of salt‐treated PPy:PSS multilayer films is attributed to charge screening and conformational change of PPy, along with the removal of excess PSS. Under standard AM 1.5 sunlight illumination, salt treatment is shown to boost the efficiency of multilayer PPy:PSS composite film‐based DSCs, leading to enhanced power conversion efficiency of 6.18, 6.33 and 6.37% for one, three and five layers, respectively. These values are significantly higher ( ca 50%) than those for corresponding devices without CuBr2 salt treatment (3.48, 2.90 and 2.01%, respectively). © 2016 Society of Chemical Industry